The Role of Satintelkam in the Restriction of Aremania Post the Kanjuruhan Tragedy at the Malang Police (Indonesian Journal of Police Studies, 2024)
The Kanjuruhan tragedy on October 1 2022, which claimed 135 lives, created deep wounds in the history of Indonesian football. The crucial role of the Malang Police Intelligence and Security Unit (Satintelkam) in identifying and preventing potential security disturbances and taking preventive action is the focus of this research. The aim of the research is to explore the role of Satintelkam in reducing potential conflict among Aremania to realize Harkamtibmas after the Kanjuruhan Tragedy and analyze the strategies implemented. This research uses a qualitative approach with interview techniques, observation and document analysis. Meanwhile, the theories used are management theory and communication theory. The concepts used are the role concept, the Satintelkam concept, and the concept of mobilization. The findings and conclusions show that the Malang Police Satintelkam has actively attempted to create conditions for Harkamtibmas by mobilizing through social assistance, dialogue and securing demonstrations, but there is still public dissatisfaction with the National Police. and the regional government, causing minor unrest among the community who are demanding justice.
Keywords: Kata Kunci : peran, penggalangan, aremania pasca tragedi kanjuruhan